An Interpretative Study of LARCs Discontinuation in Ethiopia: The Experiences of Women Accessing Contraceptives in Selected Public Health Facilities - Mihretie GS; Abebe SM; Abera M; Assefa DT (Dove Medical Press, 2023)
Getasew Sisay Mihretie,1 Solomon Mekonnen Abebe,2 Mikyas Abera,3 Daniel Tadesse Assefa4 1Department of Obstetrics and Gynecology, School of Medicine, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 3Department of Sociology, College of Social Sciences and the Humanities, University of Gondar, Gondar, Ethiopia; 4Monitoring Evaluation Research and Quality(MERQ) Consultancy PLC, Addis Ababa, EthiopiaCorrespondence: Solomon Mekonnen Abebe, University of Gondar, P.O.Box 196, Gondar, Ethiopia, Email solomekonnen@yahoo.comBackground: Discontinuation of contraception for reasons other than wanting to become pregnant is a public health concern as it affects women's autonomy in sexual and reproductive health decision making as well as gender equality. Studies identified various factors, including community perception and users' dissatisfaction that limited the reach and impact of contraceptives, primarily LARCs, on women's wellbeing. In Ethiopia, however, the reasons for early discontinuation of LARCCs are not adequately explored. Against this backdrop, this study explores the main reasons for the early discontinuation of LARCs among Ethiopian women in selected public health facilities.Methods: This study used an institution-based qualitative study design and covered selected university hospitals and health centers in Addis Ababa, Gondar, Mekelle, and Jimma. It involved in-depth interviews with 29 women aged 15- 49 to gather data and explore the decision-making processes involved in the early discontinuation of LARCs. It used description, narration and thematic interpretation as data analysis procedures.Results: Interviewees reported several reasons for early discontinuation of LARCs, including side effects (eg, weight gain/loss, heavy menses, tiredness, and reduced libido), desire to conceive, and husbands' disapproval. This study found that women were sufficiently aware of alternative contraceptives, including LARCs. Many reported experimenting before deciding on an option. Conversely, others' reports reveal the influences of gender roles and community misconceptions on women's decisions to discontinue LARCs.Discussion and Implications: The common threads in interviewees' narratives highlight the significance of traditional values, gender roles, community perception, and experience with side effects to women's early discontinuation of LARCs. This study concludes with remarks on how to improve the effectiveness of family planning programming by adopting the gender transformative approach (GTA) in their design and implementation.Keywords: contraceptive, LARCs, early discontinuation, institution-based qualitative study